The most common behavioral problems among students with academic learning difficulties in the primary stage A field study in some of the M’sila state elementary schools - khodja, asma (Journal of Social Sciences and Humanities, 2019)
The study aims to identify the most common behavioral problems among Pupils of third year’s primary school with academic learning difficulties (reading, writing, math), As well as detectation of differences of behavioral problems among them ; To achieve the objectives of the study,we applied a list of behavioral problems on Intentional sample consisted 34 pupils with academic learning difficultiesc ;including (10) reading Difficulties, (13) writing Writing Difficulties and (14) with calculation Difficulties ; The study found that: behavioral problems more prevalent among pupils with academic learning difficulties is the dispersion of attention and hyperactivity while aggressive behavior in the last place. Also the study found that there were no statistically significant differences in behavioral problems among students with learning differences in academic difficulties ( Reading - writing -arithmetic),